Scourged - Hearne, Kevin (Hearne, Kevin. Iron druid chronicles, 2018)
"Kevin Hearne creates the ultimate Atticus O'Sullivan adventure in the grand finale of the New York Times bestselling Iron Druid Chronicles: an epic battle royale against the Norse gods of Asgard. Unchained from fate, the Norse gods Loki and Hel are ready to unleash Ragnarok, a.k.a. the Apocalypse, upon the earth. They've made allies on the darker side of many pantheons, and there's a globe-spanning battle brewing that ancient Druid Atticus O'Sullivan will be hard-pressed to survive, much less win. Granuaile MacTiernan must join immortals Sun Wukong and Erlang Shen in a fight against the Yama Kings in Taiwan, but she discovers that the stakes are much higher than she thought. Meanwhile, Archdruid Owen Kennedy must put out both literal and metaphorical fires from Bavaria to Peru to keep the world safe for his apprentices and the future of Druidry. And Atticus recruits the aid of a tyromancer, an Indian witch, and a trickster god in hopes that they'll give him just enough leverage to both save Gaia and see another sunrise. There is a hound named Oberon who deserves a snack, after all. Praise for Kevin Hearne and The Iron Druid Chronicles "[The Iron Druid books] are clever, fast-paced and a good escape."--Jason Weisberger, Boing Boing "Celtic mythology and an ancient Druid with modern attitude mix it up in the Arizona desert in this witty new fantasy series."--Kelly Meding, author of Chimera "Outrageously fun."--The Plain Dealer, on Hounded "Superb. plenty of quips and zap-pow-bang fighting."--Publishers Weekly (starred review), on Hounded "An exciting mix of comedy, action, and mythology. [Atticus] is one of the best main characters currently present in the urban fantasy genre."--Fantasy Book Critic, on Tricked "Funny, razor-sharp. plenty of action, humor, and mythology."--Booklist (starred review), on Shattered"--